2018
DOI: 10.1136/archdischild-2017-314119
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ gaze behaviour in simulated paediatric emergencies

Abstract: This study is the first to describe differences in the gaze behaviour between experts and novices in a resuscitation. They mirror those described in aviation and surgery. Further research is needed to evaluate the potential use of eye tracking as an educational tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Eye-tracking can be used to assess and quantify VA as a measure of human performance within clinical settings 3 4 17–22. However, there is a lack of data on VA during neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Eye-tracking can be used to assess and quantify VA as a measure of human performance within clinical settings 3 4 17–22. However, there is a lack of data on VA during neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of this study is that it is one of the first to examine visual attention in a real-life situation in an ICU by using eye tracking [18]. A few studies have used eye tracking in critical situations, but these were simulated [6,7,[10][11][12][13][14][15][19][20][21][22][23]. Eye tracking can also be successfully integrated into electronic health record-based simulation and provides a surrogate measure of cognitive decision-making and electronic health record usability [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, eye trackers were used in multiple ways for broadening knowledge on multiple aspects of the teaching process and discovering the way for achieving fluency in performing various professional obligations [44]. The most interesting research was conducted with regard to diagnosis and improvement of professional skills of school pedagogues [45], doctors and diagnosticians of various medical specializations [46][47][48], criminologists [49], airplane pilots [50], drivers [51], and navigators of sea vessels [52].…”
Section: Eye Tracking and Educationmentioning
confidence: 99%
“…According to the studies conducted in other fields [45][46][47][48][49][50][51][52][53][54], it can be concluded that in general, architectural items are perceived in a different way by a non-professional, a student of the faculty of architecture, and a lecturer. However, conclusions from conducting such studies may be used in architectural education of all of the abovementioned groups.…”
Section: Eye Trackers In Architectural Educationmentioning
confidence: 99%